Application of Interactive Teaching Materials Based on Discovery Learning Digestion System Subjects to Improve 21st Century Skills - Desy Fatmawati; Isnaeni, Wiwi (Universitas Negeri Semarang, 2024)
21st century skills that students need to have include critical thinking abilities, learning motivation, and collaboration abilities. Class XI MIPA students at SMAN 4 Semarang are still learning using printed teaching materials, so interactive teaching materials based on Discovery Learning are needed to improve 21st century skills. This research aims to analyze the application of Discovery Learning-based interactive teaching materials on the human digestive system to improve the 21st century skills of class XI-MIPA students at SMAN 4 Semarang. The independent variable is interactive teaching materials based on Discovery Learning digestive system material. The dependent variables are students' critical thinking abilities, learning motivation, and collaboration abilities. Data were analyzed using descriptive percentages, t -test, and N-Gain Score. The research results obtained were the aspect of critical thinking ability with the greatest increase in the analysis aspect of 29%. The indicators of learning motivation with the highest percentage are readiness, persistence and enthusiasm. The collaboration ability indicators with the highest percentage are flexible (95%) and mutual respect (100%). The conclusion obtained is that the application of interactive teaching materials based on Discovery Learning material on the human digestive system can improve students' critical thinking skills, learning motivation and collaboration abilities.